1994
DOI: 10.1038/bjc.1994.479
|View full text |Cite
|
Sign up to set email alerts
|

Cancer mortality and morbidity among workers at the Sellafield plant of British Nuclear Fuels

Abstract: Summary The mortality of all 14,282 Cancer mortality rates were significantly in excess of national rates for cancers of the pleura (nine observed, 2.6 expected; P = 0.001), thyroid (six observed, 1.8 expected; P = 0.01) and ill defined and secondary sites (53 observed, 39.2 expected; P = 0.02). There were significant deficits of cancers of the liver and gall bladder, larynx and lung. Among radiation workers there were significant positive correlations between accumulated radiation dose and mortality from ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
2
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 13 publications
5
59
2
4
Order By: Relevance
“…No significant associations were reported in Sellafield, Atomic Weapons Establishment, Hanford, Japanese, or combined US, UK and Canadian cohorts. [305][306][307][308][309][310][311][312] Furthermore, there were no trends in NHL risk based on cumulative radiation dose in these cohorts. Other studies have reported no significant associations among US military personnel who participated in atmospheric nuclear weapons tests, 313 participants in the UK atmospheric nuclear weapons tests, 314 residents living near nuclear installations, 315,316 uranium miners, 317 dental workers 318 or cohort members of the National Dose Registry of Canada.…”
Section: Radiation Exposurementioning
confidence: 99%
“…No significant associations were reported in Sellafield, Atomic Weapons Establishment, Hanford, Japanese, or combined US, UK and Canadian cohorts. [305][306][307][308][309][310][311][312] Furthermore, there were no trends in NHL risk based on cumulative radiation dose in these cohorts. Other studies have reported no significant associations among US military personnel who participated in atmospheric nuclear weapons tests, 313 participants in the UK atmospheric nuclear weapons tests, 314 residents living near nuclear installations, 315,316 uranium miners, 317 dental workers 318 or cohort members of the National Dose Registry of Canada.…”
Section: Radiation Exposurementioning
confidence: 99%
“…We have described previously the study population, the nature and source of external radiation exposure data and the methods used to determine the vital status, causes of death and cancer registrations (Smith and Douglas, 1986;Douglas et al, 1994). We summarize this information briefly below, together with the details of plutonium exposure and the methods used to derive estimates of plutonium uptake and organ-specific doses.…”
Section: Population and Methodsmentioning
confidence: 99%
“…The possible carcinogenic effects of exposure to external sources of radiation among nuclear workers have been the subject of a large number of studies (Kendall et al, 1992;Gilbert et al, 1993;Carpenter et al, 1994;Cardis et al, 1995), but there have been few studies of internal exposure to radionuclides among these groups. We have reported previously on mortality and cancer morbidity among workers at the Sellafield plant of British Nuclear Fuels (BNFL) (Smith and Douglas, 1986;Douglas et al, 1994). We examined possible risks associated with exposure to external radiation, but at these times the data available on exposure to radionuclides were inadequate for detailed analysis.…”
mentioning
confidence: 99%
“…These databases are of a generally high quality, not only because radiation dose records have to be maintained for United Kingdom regulatory purposes, but also because the data have been used previously for several large epidemiological studies of the workers themselves. [15][16][17][18][19][20][21][22] Data were supplied for all those responding who had ever had, or who had ever attempted to have, children, and were linked by computer to the cleaned, coded, and validated questionnaire based data with the subjects' unique personal identifiers. Thus the researchers were blind to the occupational exposure status of the workers when collecting data on reproduction and child health outcomes.…”
Section: Study Populationmentioning
confidence: 99%
“…1-4 6 8 10 14 Generally, when an occupational hazard is suspected the health of the workers in the industries concerned is studied directly: for example, within the nuclear industry, several cohort studies have investigated the relation between cancer and mortality in relation to exposure to ionising radiation at work. [15][16][17][18][19][20][21][22] The nuclear industry family study takes this one step further, linking the occupational exposure of workers to their pregnancies and the health of their children.…”
mentioning
confidence: 99%